2017
DOI: 10.1002/ldr.2662
|View full text |Cite
|
Sign up to set email alerts
|

Tracing Sediment Sources in a Subtropical Agricultural Catchment of Southern Brazil Cultivated With Conventional and Conservation Farming Practices

Abstract: In Brazil, agricultural expansion has increased soil erosion and sediment supply to waterways. As elevated sediment loads often degrade freshwater environments, sediment fingerprinting techniques are increasingly used to identify the sources supplying sediment to riverine and lacustrine environments. In this study, the contribution of various soil types to sediment was investigated in the Guaporé catchment (2,032 km2) in southern Brazil. Soil samples (n = 75) were collected to characterise five soil types: Fer… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
19
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
8

Relationship

4
4

Authors

Journals

citations
Cited by 27 publications
(21 citation statements)
references
References 50 publications
2
19
0
Order By: Relevance
“…Results reported by Le Gall et al (2017) also show that the contribution of fine sediments from farther upstream sources on large catchments is minor, at least considering the sediments that effectively reach the catchment outlet. Such behavior must be analyzed with caution, as fingerprinting the origin of outlet sediments does not necessarily represent overland and fluvial transport processes elsewhere in the catchment (Koiter et al 2013a).…”
Section: Discussionmentioning
confidence: 83%
See 1 more Smart Citation
“…Results reported by Le Gall et al (2017) also show that the contribution of fine sediments from farther upstream sources on large catchments is minor, at least considering the sediments that effectively reach the catchment outlet. Such behavior must be analyzed with caution, as fingerprinting the origin of outlet sediments does not necessarily represent overland and fluvial transport processes elsewhere in the catchment (Koiter et al 2013a).…”
Section: Discussionmentioning
confidence: 83%
“…Although many different sediment properties have been used to identify sources, sediment elemental composition has been commonly used in fingerprinting studies to distinguish source contributions according to land use (Collins et al 2010;Voli et al 2013;Cooper et al 2015;Pulley et al 2017), geological units (Olley and Caitcheon 2000;Wilkinson et al 2013;, and, less frequently, soil classes (Evrard et al 2013;Lepage et al 2016;Le Gall et al 2017). In addition to aiding catchment management, Koiter et al (2013b) argue that the information obtained in such studies can be used to understand the underlying processes that regulate sediment transport and generate the individual geochemical signatures within sources.…”
Section: Introductionmentioning
confidence: 99%
“…Terracing is the least used conservation practice in the agricultural areas of these municipalities, although contour farming is used, with or without crop rotation (Table I). Didoné et al (2014) and Le gall et al (2017) observed that the lack of additional measures to control surface runoff, such as crop rotation and terraces, can result in erosion problems in NT areas.…”
Section: Discussionmentioning
confidence: 99%
“…Also, soil and water conservation practices, such as maintaining crop residues on soil surface, contour planting, terraces construction, reduced tillage and no tillage (Didoné, Minella and Evrard, 2017;Le Gall et al, 2016;Rocha Junior et al, 2017), are used in Brazil to control erosion and nutrient transport. In this sense, a P index classification was performed according to Table 4 ( Sharpley;Mcdowell;Kleinman, 2001).…”
Section: Management Interpretationmentioning
confidence: 99%